Moyamoya Disease Presenting as Ischemic Stroke Following Heamorrhagic Strokein a 46-year-old Man: A Case Report (Bangladesh Medical Journal, 2019)
Moyamoya is a rare cerebrovascular disease of unknown etiology. It can affect both children and adults. Ischemic symptoms are common in younger age while adults presents with intracranial hemorrhage. Cerebral ischemia after hemorrhage within a narrow time frame or simultaneous presentation with both hemorrhage and ischemia in the same clinical setting is a rare encounter. Diagnosis is confirmed by doing cerebral angiogram. Here, we report a case of 46-year-old man who presented with hemiparesis and imaging of brain showed ishaemic stroke initially and subsequently he also developed haemorrhagic stroke. Later, magnetic resonance imaging and digital substraction angiogram of brain confirmed Moyamoya disease. He was managed conservatively with significant improvement of his hemiparesis.Bangladesh Med J. 2019 Jan; 48 (1): 54-58